Patterns and causes of maternal mortality in tertiary care hospital in Maharashtra, India: a 10-year retrospective study - Wakode, Shamrao Ramji; Sharma, Sakshi Pramod; Patil, Apurva Shankarrao; Kiran, P. Manisha (International Journal of Research in Medical Sciences, 2023)
Background: Maternal death is a catastrophe, as death of a mother can the entire family. The aim of present study is to find out major patterns, reasons and complications leading to maternal deaths. Methods: A retrospective study was conducted for last 10 years from January 2013 to December 2022 by studying the records of a tertiary care hospital to study the maternal mortalities and complications leading to death. Maternal deaths were analyzed by considering different facets, such as age at death, gravida, locality of residence, admission death interval and direct and indirect cause/s of death, etc. Results: During the study period, total of 107753 live births and 202 maternal deaths have been recorded. The average maternal mortality rate of last ten years was 187.46/100000 live births. Age wise maternal mortality during the study period was high in the age 19 to 25. Major direct cause of maternal mortality was postpartum hemorrhage, (23%) and major indirect cause observed was anemia (43%). Admission to death interval time indicates that delay in provision of treatment and referral to tertiary care hospital might be the reason responsible for high maternal deaths. Conclusions: Maternal deaths can be prevented by improving the health care facilities, ensuring skilled attendants and required basic medication. This is high time to mobilize universal, national, regional, and community-based commitment to decrease maternal mortalities.